Odpowiedzi

Najlepsza Odpowiedź!
2009-11-22T12:43:26+01:00
Wykonaj mnożenie:
a) (√5-√3)(√5+√3)=5-3=2
b) (√7+4)(4+√7)=7+8√7+16=23+8√7
c) (√11+2)(√11-2)=11-4=7
d) (2√2-1)(2√2+1)=8-1=7
e) (√15-√6)(√5-√2)=√75-√30-√30+√12=5√3-2√30+2√3=7√3-2√30
f) (√20-√18)(√20+√18) =20-18=2
2009-11-22T12:49:11+01:00
Ze wzoru skróconego mnożenia:
a) (√5-√3)(√5+√3)=√5²-√3²=5-3=2
b) (√7+4)(4+√7)=√7²+8√7+4²=7+16+8√7=23+8√7
c) (√11+2)(√11-2)=√11²-2²=11-4=7
d) (2√2-1)(2√2+1)=2√2²-1²=8-1=7
e) (√15-√6)(√5-√2)=√75-√30-√30+√12=√75-2√30+√12
f) (√20-√18)(√20+√18)
2009-11-22T12:58:59+01:00
A) (√5-√3)(√5+√3)=5-3=2

b) (√7+4)(4+√7)=7+8√7+16 = 23+8√7

c) (√11+2)(√11-2)=11-4=7

d) (2√2-1)(2√2+1)=8-1=7

e) (√15-√6)(√5-√2)=√3(√5-√2)(√5-√2) = √3(5-2√10+2) = 7√3-2√30

f) (√20-√18)(√20+√18)= 20-18=2


Pozdrawiam! :)